Capacitive-discharge pumped CuBr laser with 12 W average output power; IEEE Journal of Quantum Electronics; Vol. PP, iss. 99 - Gubarev F. A. Fedor Aleksandrovich; Shiyanov D. V. Dmitry Valeryevich; Sukhanov V. B. Viktor Borisovich; Evtushenko G. S. Gennady Sergeevich (2012, 2012)
This paper presents the study of the energy characteristics of a medium scale CuBr laser (1130 ñm3 active volume) pumped by a longitudinal capacitive discharge. The output power dependences on the equivalent operating capacitance and on the ratio of high-voltage and ground electrode capacitances are studied. The best characteristics are obtained when the high-voltage electrode capacitance exceeds the ground electrode capacitance or when the electrode capacitances are equal. The presence of a threshold value for pumping power, above which the introduction of HBr additive into the active volume improves laser performance, is also noted. The total maximum average lasing power was 12 W at ~0.5% efficiency when the capacitances of both electrodes were 1190 pF.